Hybrid based Small Wind Generator with Boost Converter System - Senthilkumar, P.; Emayavaramban, G.; Amudha, A.; Siva Ramkumar, M.; Viyathukattuva; Viyathukattuva; Nagaveni, P.; Nivetha, M. (International Journal of Psychosocial Rehabilitation, 2019)
Design of boost converter integrated with solar panel system and small wind generator based on hybrid techniques are presented in this paper. In a wind turbine, with full-bridge DC to DC converter, they are implemented. Converter performance is enhanced by adding DC to DC converter with passive filter. In DC to DC converter, medium frequency transformer’s voltage stress is minimized effectively by this passive filter. Also presented a dc to dc converter based wind turbine control in a dc –grid system. MATLAB is used for the implementation proposed system. On DC-DC Boost Converter, enhancement in power is indicated by the results of simulation. In MATLAB/SIMULINK environment, simulated the proposed system.